Screening Extremely Obese Pregnant Women for Obstructive Sleep Apnea. Issue 3 (September 2019) - Dominguez, J.E.; Grotegut, C.A.; Cooter, M.; Krystal, A.D.; Habib, A.S.
Abstract : ( Am J Obstet Gynecol . 2018;219:613.e1.1–10) Obstructive sleep apnea (OSA), in addition to its multiple comorbidities, is associated with a significantly increased risk of preeclampsia and gestational diabetes mellitus in obese, pregnant women. However, current OSA diagnostic tools are costly and time-consuming to implement on a wide scale, and although portable at-home, unattended sleep apnea testing is emerging, such tools may be impractical in this particular patient population. This study evaluated the validity of existing OSA screening tools in a cohort of extremely obese pregnant women [body mass index (BMI) ≥40 kg/m 2 ] and determined what screening factors were most strongly associated with OSA in this cohort.